2006
DOI: 10.1080/14764170600719775
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic skin flattening (PSF): A novel technology for marked pain reduction in hair removal with high energy density lasers and IPLs

Abstract: PSF significantly reduces pain in all patients, even when higher (+30%) treatment energy levels are applied. Skin is well protected thermally by the conductive sapphire window. Post erythema and edema is considerably reduced, as well. Hair removal efficacy is preserved or enhanced. Treatment is faster and is uninterrupted by pain, without the necessity to apply topical anesthetic over a large area. Blood expulsion resulting from flattening the skin has also enabled the treatment of thin hair in light-skinned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…These authors also demonstrated decreased erythema posttreatment when using PSF, and reported that PSF resulted in equivalent or greater hair reduction than was noted without PSF use when evaluated post-treatment [16]. The likelihood that activating pressure receptors reduces the sensation of pain is supported by the fact that devices that produce pressure on the skin by vibration, but without suction, also reduce the sensation of pain felt during a procedure [15].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…These authors also demonstrated decreased erythema posttreatment when using PSF, and reported that PSF resulted in equivalent or greater hair reduction than was noted without PSF use when evaluated post-treatment [16]. The likelihood that activating pressure receptors reduces the sensation of pain is supported by the fact that devices that produce pressure on the skin by vibration, but without suction, also reduce the sensation of pain felt during a procedure [15].…”
Section: Discussionmentioning
confidence: 81%
“…Lask et al [16] reported substantial pain reduction when using the PSF device and achieving 500 mm HG of negative pressure, and using the device with an IPL, 810 nm diode laser, and a 755 nm alexandrite laser for hair reduction. These authors also demonstrated decreased erythema posttreatment when using PSF, and reported that PSF resulted in equivalent or greater hair reduction than was noted without PSF use when evaluated post-treatment [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations